Three new species of Itagonia Reitter, 1887 (Coleoptera, Tenebrionidae: Blaptini) from Sichuan, China - Shi, Ai-Min; Yuan, Shi-Bin; Wu, Chun-Lian (Zootaxa, 2010)
Three new species of Itagonia Reitter, 1887, I. tuberculata, sp. nov., I. xinlongensis, sp. nov. and I. medvedevi, sp. nov. are described from Sichuan, China. The formerly unknown female of I. elegans Medvedev, 1998 is described for the first time. A key to the known species of Itagonia from China is given.